Experiencing racism: exploring discrimination through the eyes of college students - Seltzer, Richard (Lexington Books)
"Experiencing Racism provides a thought-provoking and thorough analysis of how race is lived in America. Collecting essays on personal experiences of race and racism from a wide spectrum of college students, the authors employ existing social science literature and textual analysis to illustrate common themes and departures. The essays and associated analyses capture the impact of racism on its perpetrators and victims, highlighting how individuals choose to cope with racist experiences in their lives. Relevant empirical literature is interwoven throughout the chapters to demonstrate the intersection between existing empirical research and real-life experiences. This book is a depiction of race in America that goes beyond black and white to show how the changing racial contours of America are impacting the ways we view and experience racism."--Page 4 of cover